Parametrization in Models of Subcritical Glass Fracture: Activation Offset and Concerted Activation - Rodrigues, Bruno Poletto; Hühn, Carolin; Erlebach, Andreas; Mey, Dorothea; Sierka, Marek; Wondraczek, Lothar (Frontiers in Materials, 2017)
There are two established but fundamentally different empirical approaches to parametrize the rate of subcritical fracture in brittle materials. While both are relying on a thermally activated reaction of bond rupture, the difference lies in the way as to how the externally applied stresses affect the local energy landscape. In the consideration of inorganic glasses, the strain energy is typically taken as an off-set on the activation barrier. As an alternative interpretation, the system’s volumetric strain-energy is added to its thermal energy. Such an interpretation is consistent with the democratic fiber bundle model. Here, we test this approach of concerted activation against macroscopic data of bond cleavage activation energy, and also against ab initio quantum chemical simulation of the energy barrier for cracking in silica. The fact that both models are able to reproduce experimental observation to a remarkable degree highlights the importance of a holistic consideration towards non-empirical understanding.